2020
DOI: 10.4103/psychiatry.indianjpsychiatry_573_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sympathetic sudomotor responses to auditory stimuli in children with autism spectrum disorders

Abstract: Aim and Objective: Autism spectrum disorder (ASD) being a complex neurological and developmental disorder is also associated with autonomic nervous system dysfunction. Sudomotor nerve function is one highly sensitive index of sympathetic cholinergic activity and can be evaluated by measuring sympathetic skin response (SSR) to various stimuli. Studies reporting SSR to auditory stimulus among ASDs are limited and to the extent of our knowledge not assessed in the Indian scenario. The objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Impairments at the level of emotional perception can be related to internal distractions or overload of sensory information that hinder social communication. Studies using sympathetic skin response show that children diagnosed with ASD exhibit delayed habituation to auditory stimuli (Bharath et al 2021 ). The predominant state of sympathetic nerves can affect the predisposition to filter and perceive cues, and also influence anxiety levels or valence of social cues.…”
Section: Results and Critical Discussionmentioning
confidence: 99%
“…Impairments at the level of emotional perception can be related to internal distractions or overload of sensory information that hinder social communication. Studies using sympathetic skin response show that children diagnosed with ASD exhibit delayed habituation to auditory stimuli (Bharath et al 2021 ). The predominant state of sympathetic nerves can affect the predisposition to filter and perceive cues, and also influence anxiety levels or valence of social cues.…”
Section: Results and Critical Discussionmentioning
confidence: 99%
“…In this context, the autonomic nervous system (ANS) plays a crucial role in the control of the physiological, emotional/ cognitive and behavioural state during social interaction. Recently, scientists' interest in detecting relationships between autonomic dysfunction and ASD has been growing, but the exact pathomechanisms leading to autonomic abnormalities in ASD are still unclear (Bal et al 2010;Ming et al 2011;Plus 2019;Bharath et al 2020). Moreover, the existing findings on the ASD-linked sympathetic regulation reflected by EDA are controversial, such as increased, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the existing findings on the ASD-linked sympathetic regulation reflected by EDA are controversial, such as increased, i.e. associated with more social impairments (O'Haire et al 2015;Neuhaus et al 2016;Fenning et al 2017), unaltered (Kong et al 2021), decreased (linked with augmented externalizing behaviour complications in ASD children) (Bujnakova et al 2016;Baker et al 2018), or slower habituation of sympathetic skin response to auditory stimuli indicating a persistent predominant state of sympathetic activity in autism (Bharath et al 2020). Furthermore, Baker et al (2015) found positive associations of EDA and interpersonal variability (i.e.…”
Section: Introductionmentioning
confidence: 99%